2016
DOI: 10.1016/j.chest.2015.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-Induced Sarcoid-Like Granulomatous Reaction in a Patient With Advanced Melanoma

Abstract: To our knowledge, we report the first case of sarcoid-like granulomatous reaction induced by nivolumab, a fully human IgG4 anti-programmed death 1 (PD-1) immune checkpoint inhibitor antibody. A 57-year-old man was treated with nivolumab 3 mg/kg for 2 weeks for a desmoplastic melanoma stage III American Joint Commission on Cancer, with no BRAF, NRAS, and cKit mutations. At 10 months, although melanoma complete response was achieved, he developed sarcoid-like granulomatous reaction in the mediastinal lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 19 publications
3
91
1
1
Order By: Relevance
“…We used nivolumab as a second-line treatment for recurrent lung cancer and observed the development of granulomatous lesions. Sarcoidosis and sarcoid-like reactions have been reported when nivolumab is used alone or in combination with ipilimumab in the treatment of melanoma [1, 2, 3, 4]. It has also been reported that sarcoidosis can develop following pembrolizumab treatment in sarcoma [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used nivolumab as a second-line treatment for recurrent lung cancer and observed the development of granulomatous lesions. Sarcoidosis and sarcoid-like reactions have been reported when nivolumab is used alone or in combination with ipilimumab in the treatment of melanoma [1, 2, 3, 4]. It has also been reported that sarcoidosis can develop following pembrolizumab treatment in sarcoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…This was a strong indication that the granuloma was a side effect of nivolumab treatment. As improvement was observed by discontinuation of nivolumab alone, we did not administer steroid treatment [3]. Additionally, follow-up observation indicated that the primary lesion did not progress after the discontinuation of nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cases of sarcoid-like reactions have been reported following treatment of melanoma with interferon, vemurafenib, vaccine therapy, ipilimumab and nivolumab [9][10][11][12][13][14]. In our institutional experience, we have seen patients with concurrent melanoma and sarcoidosis both identified at the diagnosis of malignancy, and the development of sarcoid-like reactions, both symptomatic and asymptomatic from ICPI therapy [15].…”
mentioning
confidence: 89%
“…Pseudoprogression, also called tumor flare, is a distinct immune-related pattern of response caused by the infiltration of immune cells to the tumor site that can manifest in the form of an apparent increase in tumor size, the development of new lesions, or a mixed response such as progression and regression of different tumors in the same patient [112,113]. The development of granulomatous changes in the lymph nodes resembling progression have also been described during immunotherapy treatment [114]. In studies investigating immunotherapies in patients with cancer, the prevalence of pseudoprogression can vary based on tumor type; for example, it has been reported to be 7% to 10% in melanoma [23,113,115], 5% to 7% in NSCLC [25,27], 7% in UC [54], and 0% to 2% in HNSCC [44,116].…”
Section: Pseudoprogression With Icbsmentioning
confidence: 99%